The concept of elite and democracy in the political thought of the Republic of Lithuania in the period of 1918-1940 - Šiliauskas, Saulius (Politologija, 1998)
The transformation of democratic theory in the early XXth century is bound to the model of Competitive Elitism. The article deals with the situation of Lithuanian Political Thought in the Republic of Lithuania (1918-1940). The author is interested in reflecting on the concept of the Modern Democracy in Lithuania during this period.Within variable political trends, the problem of effective political leadership came to be discussed in the context of ideological polemics. The Nationalist-trend ideologists rejected deliberately the method of legal authority legitimation and better preferred traditional and charismatic ones. Save declaring the idea of the "Nation’s Leader," radical Nationalists failed to provide for the change of authoritarian regime to totalitarian one. The Left-wing democratic thought interpreted elections as a method of authority selection and legitimation. They believed that the elitist democracy goes at variance with the normative theory of democracy. On its side, Christian democratic thought had little in common with a more realist elitist concept of democracy. However, by reason of antiliberalist character, these ideas were never developed.The author states that there was an insufficient number of social-political and methodological-theoretical preconditions to incite a more realist interpretation of modern democracy in Lithuanian political thought of the period. The majority of Lithuanian political elite rejected the notion of liberal democracy. Therefore, the democratic thought failed to overcome a perfectionist attitude towards democracy, thus real political processes of democracy functioning in the hierarchical structure of governing remained unanalysed. The main conclusion of this article is that the opportunity to modernise political thinking and thus get closer to modern democratic thought was missed.